Antitumor activity of the poly(ADP-ribose) polymerase inhibitor rucaparib as monotherapy in patients with platinum-sensitive, relapsed, BRCA-mutated, high-grade ovarian cancer, and an update on safety. Issue 9 (3rd November 2019) - Kristeleit, Rebecca S; Oaknin, Ana; Ray-Coquard, Isabelle; Leary, Alexandra; Balmaña, Judith; Drew, Yvette; Oza, Amit M; Shapira-Frommer, Ronnie; Domchek, Susan M; Cameron, Terri; Maloney, Lara; Goble, Sandra; et al.
Abstract : Objective: To report results from an integrated efficacy and safety analysis supporting the European Commission's approval of the poly(ADP-ribose) polymerase inhibitor rucaparib as monotherapy treatment for relapsed, platinum-sensitive, BRCA -mutated ovarian cancer. Methods: Efficacy was analyzed in platinum-sensitive patients from Study 10 (NCT01482715 ) and ARIEL2 (NCT01891344 ) who had high-grade serous or endometrioid epithelial ovarian, fallopian tube, or primary peritoneal cancer and a deleterious BRCA1 or BRCA2 mutation and received two or more prior chemotherapies (including two or more platinum-based therapies). The primary end point was investigator-assessed, confirmed objective response rate (visit cut-off: April 10, 2017). Safety was analyzed in patients with ovarian cancer, regardless of BRCA mutation status or lines of prior chemotherapies, who received at least one dose of rucaparib 600 mg in either study (visit cut-off: December 31, 2017). Results: In the integrated platinum-sensitive efficacy population (n=79), objective response rate was 64.6% (95% CI, 53.0 to 75.0); 10.1% (8/79) of patients had a complete response and 54.4% (43/79) had a partial response. Median duration of response was 294 days (95% CI, 224 to 393). In the integrated safety population (n=565), the most common any-grade treatment-emergent adverse events were nausea (77.7%, 439/565), asthenia/fatigue (74.7%, 422/565), vomiting (45.8%, 259/565), and hemoglobin decreased (44.2%, 250/565). Treatment-emergent adverse events led to treatment interruption, dose reduction, or discontinuation in 60.2% (340/565), 46.0% (260/565), and 16.8% (95/565) of patients. Conclusions: In patients with platinum-sensitive, BRCA -mutated ovarian cancer, rucaparib demonstrated antitumor activity and is the first and currently the only poly(ADP-ribose) polymerase inhibitor approved by the European Commission as treatment for this population. The safety analysis used a more recent visit cut-off date and larger population than previously published, was consistent with prior reports, and was the basis for the treatment-indication safety population in rucaparib's recently updated European Union label.